Development of Learning Media Using Canva in Class XI Science at MAN 2 Bukittinggi - Nabilah*, Bunga; Supriadi, Supriadi; Zakir, Supratman; Efriyanti, Liza (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
Media is a very important element in learning. The use of teaching materials in learning is increasing along with technological developments, such as applications and software that allow teachers to create attractive classrooms and increase student interest in learning. The application chosen to be used to create interesting and simple learning materials is Canva. These applications meet various needs in the fields of graphics, business, advertising, technology, management, and education. In subjects such as biology where there are lots of pictures and explanations about human organs, the use of interesting learning media is very important. Therefore, the purpose of this research is to create biology learning media using Canva for class XI IPA students at MAN 2 Bukittinggi. This study uses the research and development (RnD) method with the Luther-Sutopo development model. The results showed that the average test value for the validity of the biology learning environment developed using Canva for class XI IPA MAN 2 Bukittinggi was 0.82 which indicated that this media was very valid. In addition, this media was found to be very practical with an average practicality test value of 0.90, and efficient with an average efficiency test value of 0.90. Based on the results of testing these educational media products, it can be concluded that the use of Canva can help the learning process and is beneficial for teachers and students.